2012
DOI: 10.1590/s0103-64402012000600012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluoride solutions on the shear bond strength of orthodontic brackets

Abstract: The aim of this in vitro study was to evaluate the shear bond strength of brackets after pre-treatment with different fluoride solutions. This study used 48 freshly extracted sound bovine incisors that were randomly assigned to 4 experimental groups (n=12). CG: (control) without treatment; NF: 4 min application of neutral fluoride; APF: application of 1.23% acidulated phosphate fluoride (APF) for 4 min; and SFV: application of 5% sodium fluoride varnish for 6 h. For each group, after surface treatment, prophyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…The prior application of 1.23% APF resulted in a statistically significant reduction in bond strength independently of the adhesive system, which is in agreement with data described in the literature (18). Among the different types of high concentration fluoride compounds, it is observed in the literature (8), that the 1.23% APF gel and 5% sodium fluoride varnish promote reduction in the bond strength values when compared to untreated and teeth treated with 2% neutral fluoride gel. Previous studies suggest that maximum adhesion of composite resins to dental enamel is achieved when acid etching is performed two weeks after the application of APF (9,10).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The prior application of 1.23% APF resulted in a statistically significant reduction in bond strength independently of the adhesive system, which is in agreement with data described in the literature (18). Among the different types of high concentration fluoride compounds, it is observed in the literature (8), that the 1.23% APF gel and 5% sodium fluoride varnish promote reduction in the bond strength values when compared to untreated and teeth treated with 2% neutral fluoride gel. Previous studies suggest that maximum adhesion of composite resins to dental enamel is achieved when acid etching is performed two weeks after the application of APF (9,10).…”
Section: Discussionsupporting
confidence: 89%
“…The application of fluoride solutions prior to restorative treatment can affect the adhesive strength of the material. In a study involving bovine enamel, the prior application of a fluoride varnish and 1.23% APF led to a reduction in the bond strength of resin materials (8). APF is also reported to diminish surface roughness on the enamel of both primary and permanent teeth (9,10), which can affect the adhesion of composite resins.…”
Section: Introductionmentioning
confidence: 99%
“…Two standard fluoride solutions with concentrations of 5 mg.L -1 and 10 mg.L -1 were used to calibrate the measuring device (Orion 710 digital ionanalyzer; Orion Research Inc., Beverly, MA, USA) (16). Once calibrated, the analyzer performed the analyses of the specimen media, which were transferred to new sterilized containers with 10 mL of a total ionic strength adjustment buffer solution (TISAB) under constant agitation.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro studies have shown fluoride release from adhesive systems, suggesting that these materials have some effect in the enamel and dentin remineralization process and contribute to the control of secondary caries (2,(13)(14)(15)(16)(17). A previous study evaluated fluoride release behavior and the demineralization inhibition capacity of two adhesive systems and the conclusion was that adhesive systems have a fluoride-releasing behavior as they were able to reduce dental tissue demineralization after acid exposure (8).…”
Section: Introductionmentioning
confidence: 99%
“…e optimal bonding force between the bracket and enamel surface should be sufficient to enable a durable bracket position during treatment and to prevent the enamel from iatrogenic damage during the debonding procedure. Bond failures may be caused by numerous factors, including masticatory forces, forces produced by orthodontic appliances, aging of the orthodontic adhesives, mistakes during any step of bonding protocol, or some conservative dentistry therapies performed prior to bonding, such as topical fluoride varnish applications, or bleaching [7][8][9]. e range of the desired bonding force has not been determined yet.…”
Section: Introductionmentioning
confidence: 99%